2017
DOI: 10.1371/journal.pone.0175331
|View full text |Cite
|
Sign up to set email alerts
|

Identification of neovascularization by contrast–enhanced ultrasound to detect unstable carotid stenosis

Abstract: BackgroundPlaque neovascularization accompanies local inflammation and critically contributes to plaque instability. Correct identification of intraplaque neovascularization by contrast–enhanced ultrasound (CEUS) may provide an additional risk marker in carotid stenosis. This pilot study investigates the correlation between histological evaluation of carotid plaque specimens and pre-surgery CEUS to identify neovascularization.Methods17 patients with high-grade internal carotid artery (ICA) stenosis were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 34 publications
(50 reference statements)
0
46
0
Order By: Relevance
“…A clinical study demonstrated that with intraplaque hypermetabolism, high-oxygen consumption macrophages more easily produce a hypoxic microenvironment compared with increased intima-media thickness [32]. Oxygen diffusive disorder in thickened intima-media and increased oxygen consumption of inflammatory cells both lead to a hypoxic microenvironment state and stimulate neovascularization, intraplaque hemorrhage, and the rupture of atherosclerotic plaques [7]. A recent study showed that the adventitia not only provides structural support for the vessel walls but also facilitates atherosclerosis, as well as the formation of neo-intima and vulnerable plaques by "outside-in" inflammatory cells and the transfer of fibroblasts [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical study demonstrated that with intraplaque hypermetabolism, high-oxygen consumption macrophages more easily produce a hypoxic microenvironment compared with increased intima-media thickness [32]. Oxygen diffusive disorder in thickened intima-media and increased oxygen consumption of inflammatory cells both lead to a hypoxic microenvironment state and stimulate neovascularization, intraplaque hemorrhage, and the rupture of atherosclerotic plaques [7]. A recent study showed that the adventitia not only provides structural support for the vessel walls but also facilitates atherosclerosis, as well as the formation of neo-intima and vulnerable plaques by "outside-in" inflammatory cells and the transfer of fibroblasts [33].…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced ultrasound (CEUS) provides direct visualization of the IPN in carotid plaques [6]. A number of studies have recently described a positive correlation between the histological density of neovessels and the presence of neovascularization in carotid plaques detected by CEUS [7].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, intensity of enhancement corresponding to intraplaque vessel content, and wash‐in‐time reflecting the speed of flow within the plaque, were significantly associated with stroke risk . Importantly, intraplaque enhancement in contrast‐enhanced ultrasound studies correlates well with histologically verified intraplaque neovascularization and hemorrhage as well as macrophage infiltration …”
Section: Neurosonology Applications In Diagnosis and Risk Stratificationmentioning
confidence: 91%
“…The method includes injection of a contrast agent consisting of microbubbles, and the subsequent identification of micorbubbles within the vessels of the plaque after they have entered the arterial system through the pulmonary circulation . Both visual grading and semiautomated techniques have been used to evaluate neoangiogenesis . Huang et al proposed a classification method to quantify the intensity of intraplaque enhancement as grade I for plaques with no enhancement, grade II with only arterial wall vasa vasorum enhancement, grade III with arterial wall vasa vasorum and plaque shoulder enhancement, and grade IV with extensive and internal plaque enhancement.…”
Section: Neurosonology Applications In Diagnosis and Risk Stratificationmentioning
confidence: 99%
“…The analysis concerning the degree of intraplaque neovessels reported that some quantitative parameters on CEUS could replace qualitative visual scoring [4]. A pilot study indicated the association of the quantitative assessment of neovascularization with intraplaque hemorrhage [5]. Furthermore, a meta-analysis reported that CEUS is a useful, noninvasive modality for the diagnosis of intraplaque neovascularization [6].…”
Section: Doi: 101159/000495299mentioning
confidence: 99%